A bibliometric approach to Sustainable Development Goals (SDGs) systematic analysis - Faida Indana; Reza Widhar Pahlevi (Cogent Business & Management, 2023)
In this study, research on the Sustainable Development Goals (SDGs) will be carefully analyzed from the perspectives of keywords, research locations and subjects, as well as the research methodologies employed. Four key findings are presented after reviewing 347 scientific articles in this investigation. The economic and social effects of achieving the SDGs are the first theme in sustainable development research, and the added value of established plans is the second theme. Second, the most often utilized data sets are exploratory and case studies. Third, there are nearly equal numbers of studies on the Sustainable Development Goals (SDGs) in industrialized and developing nations. Fourth, based on VOSviewer-based bibliometric methods. Recommendations for more research to develop the theoretical and methodological. It will further contribute to the creation of the Sustainable Development Goals (SDGs) in the future by examining these four issues.
Keywords: 650; bibliometric analysis; Sustainable Development Goals (SDGs); economic and social impacts; VOSviewer